2015 IEEE International Symposium on Circuits and Systems (ISCAS) 2015
DOI: 10.1109/iscas.2015.7168688
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of the classical phase-locked loop analysis

Abstract: Abstract-Nonlinear analysis of the classical phase-locked loop (PLL) is a challenging task. In classical engineering literature simplified mathematical models and simulation are widely used for its study. In this work the limitations of classical engineering phase-locked loop analysis are demonstrated, e.g., hidden oscillations, which can not be found by simulation, are discussed. It is shown that the use of simplified dynamical models and the application of simulation may lead to wrong conclusions concerning … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…It has been shown that 1) the consideration of simplified mathematical models, constructed intuitively, and 2) the application of non rigorous methods of analysis (e.g., simulation and linearization) can lead to wrong conclusions concerning the operability of the Costas loop physical model. Similar result can be obtained for the classic PLL and QPSK Costas loop (see, e.g., [11], [25], [26]). …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It has been shown that 1) the consideration of simplified mathematical models, constructed intuitively, and 2) the application of non rigorous methods of analysis (e.g., simulation and linearization) can lead to wrong conclusions concerning the operability of the Costas loop physical model. Similar result can be obtained for the classic PLL and QPSK Costas loop (see, e.g., [11], [25], [26]). …”
Section: Discussionsupporting
confidence: 84%
“…While Assumption 1 is reasonable from a practical point of view, its use in the analysis of Costas loop requires further consideration (see, e.g., [10], [11]). Various averaging methods (see, e.g., [12]) allow one to justify Assumption 1 and obtain conditions under which it can be used rigorously (see [13], [14]).…”
Section: Classical Engineering Consideration Of the Costas Loop Omentioning
confidence: 99%
“…Also the errors caused by numerical integration (e.g. in MATLAB and SPICE) can lead to unreliable results [28,29,50,51].…”
Section: Remarks On Simulation Of Bpsk Costas Loopmentioning
confidence: 99%
“…classical books [12, p.12,p15-17], [13, p.7]) while it may lead to unreliable results (see, e.g. [14], [15]). …”
Section: Accepted To Ieee 7th International Congress On Ultra Modern mentioning
confidence: 99%